2016
DOI: 10.1180/minmag.2016.080.035
|View full text |Cite
|
Sign up to set email alerts
|

The relative stabilities of A- and B-type carbonate substitution in apatites synthesized in aqueous solution

Abstract: Carbonated calcium apatites doped with a monovalent cation (Li+, Na+, or K+) or a divalent cation (Mg2+ or Zn2+) were prepared in aqueous solution and analysed by powder X-ray diffraction, inductively coupled plasma atomic emission spectroscopy and infrared spectroscopy. The hypothesis that the location of carbonate in the apatite structure, either in place of hydroxide ions in the c-axis channels (A-type substitution) or in place of phosphate (B-type substitution), is affected by the solution energetics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…8,49-52,54-56 Assignment of peak 3b (1456-1447 cm À1 ) to literature data does not have such a clear consensus, with studies assigning this to both A-type substitution 49,51,56 and B-type substitution. 50,54,55 In our own recent study, A-type carbonate substituted hydroxyapatites produced peaks at approximately 1532 and 1465 cm À1 with similar peak areas. 57 The peak area of the peak in the 1557-1523 cm À1 region in the current study contributes a much smaller amount to the total peak area of the v 3 region than the peak at 1456-1447 cm À1 , Table S8 (ESI †), suggesting that the latter peak reflects some contribution of A-type carbonate in this region but relates more to B-type carbonate.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…8,49-52,54-56 Assignment of peak 3b (1456-1447 cm À1 ) to literature data does not have such a clear consensus, with studies assigning this to both A-type substitution 49,51,56 and B-type substitution. 50,54,55 In our own recent study, A-type carbonate substituted hydroxyapatites produced peaks at approximately 1532 and 1465 cm À1 with similar peak areas. 57 The peak area of the peak in the 1557-1523 cm À1 region in the current study contributes a much smaller amount to the total peak area of the v 3 region than the peak at 1456-1447 cm À1 , Table S8 (ESI †), suggesting that the latter peak reflects some contribution of A-type carbonate in this region but relates more to B-type carbonate.…”
Section: Resultsmentioning
confidence: 63%
“…Analysis was only performed on samples that were single-phase apatites by XRD analysis Design x View Article Online (0.51 wt%) and carbonate ion (5.99 wt%) contents that were comparable to x = 0.5 of Series II in this study (Table S6, ESI †) and, without peak deconvolution, identified carbonate vibrations at 1490 and 1540 cm À1 that were assigned to A-type and 1417 and 1451 cm À1 that were assigned to B-type carbonate. 54 A band at 1387 cm À1 has been assigned to carbonate in a water compartment, described as within water trapped in pores within grains, or water that is surface adsorbed 49 and, as a weak vibration from the presence of water was visible, this is feasible. No vibrations characteristic of calcite or aragonite were observed at B713 or 700 cm À1 in any of these spectra, confirming the absence of a calcium carbonate impurity in these samples; 59 a peak at 714 cm À1 was observed in the spectrum of the x = 3.0 sample of Series I (data not shown), which showed an impurity of calcite by XRD (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En la literatura científica se encuentra reportado que la apatita ósea y sus análogos durante la precipitación a temperatura corporal, la mayor parte del carbonato (CO 3 -2 ) se aloja en el sitio del fosfato (PO 4 -3 ). Sin embargo, también se observa una correlación inversa entre las concentraciones de CO 3 -2 y OHen las bioapatitas, debido a que la sustitución de x moles de fosfato por carbonato equilibra a través de y moles de vacantes tanto en el sitio del calcio como del hidroxilo (Pasteris, 2008;Yoder, 2016). La sustitución iónica de las apatitas óseas, funge como un depósito de iones de calcio y ortofosfato, los cuales son necesarios para la amplia variedad de funciones metabólicas, que ofrecen o consumen dichos iones, a través de un llamado proceso de ¨remodelación¨ debido a una continua reabsorción de formación de nanopartículas de apatita por los osteoclastos y osteoblastos respectivamente.…”
Section: Génesis De Tejido óSeounclassified
“…. [24,25] The substitution of the carbonate ion by the phosphate ion, induces different interactions in the crystal lattice due to the anion molecular geometry: the CO 3 2À species has a planar structure while the one of the PO 4 3À entity is tetrahedral. These rearrangements conduce to stabilize the crystal structure that slightly modify the cell parameters without changing the space group.…”
Section: Quantitative X-ray Diffraction Analysismentioning
confidence: 99%